2001
DOI: 10.1007/s004280100496
|View full text |Cite
|
Sign up to set email alerts
|

Nerve fibers in tumors of the human urinary bladder

Abstract: Abstract. Exophytic tumors of the urinary bladder were examined by means of transmission electron microscopy for the presence of neural tissue because, as yet, there has been hardly any discussion of a neuronal component in the biology of neoplasms. In the stroma and rarely in the epithelium of bladder tumors, fine nerve strands were found to be irregularly distributed. These strands comprised one to a maximum of five axons containing predominantly colocalized clear and dense-core vesicles. Immunohistochemistr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
0

Year Published

2003
2003
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(24 citation statements)
references
References 38 publications
1
23
0
Order By: Relevance
“…This indicates that cancer-related neurogenesis does occur in breast cancer, which is similar to previously reported observation that active neurogenesis occur in prostate cancer [4], colorectal cancer [5], esophageal and cardiac carcinoma [11], tumors of the human urinary bladder [12] and choroidal melanoma [13]. Taken together, this novel phenomenon that cancer initiates its own innervations may be universal.…”
Section: Discussionsupporting
confidence: 87%
“…This indicates that cancer-related neurogenesis does occur in breast cancer, which is similar to previously reported observation that active neurogenesis occur in prostate cancer [4], colorectal cancer [5], esophageal and cardiac carcinoma [11], tumors of the human urinary bladder [12] and choroidal melanoma [13]. Taken together, this novel phenomenon that cancer initiates its own innervations may be universal.…”
Section: Discussionsupporting
confidence: 87%
“…Under a transmission electron microscope, a small number of fine unmyelinated nerve fibers were found containing clear and dense core vesicles in tumors. Recently, they examined the exophytic tumors of the urinary bladder and human choroidal melanoma [24,25] , and also found irregularly distributed fine nerve strands comprised of axons; hence they concluded that tumors may be innervated. In this regard, they happened to have the same view with us.…”
Section: Discussionmentioning
confidence: 99%
“…32 In general, nerve fibers have been rarely observed in human tumors. [33][34][35] Interestingly, in adrenal cortical tumors, also known to express NPY receptors, 10 nerve fibers have been identified that were also shown to contain NPY. 35 These reports, together with the present results, demonstrate that NPY-positive nerve fibers can grow into certain human tumors.…”
Section: Discussionmentioning
confidence: 99%